PENGARUH PEMBERIAN EKSTRAK DAN INFUSA DAUN KELOR(Moringa oleifera) TERHADAP KADAR MALONDIALDEHID (MDA) HEPAR MENCIT OBESITAS YANG DIINDUKSI 2-NITROPROPANE - Nurdiza Bilqis (2019)
Excessive fat accumulation in obesity is a low-level chronic inflammation which can cause an increase in oxidative stress. Moringa oleifera leaves are known to have antioxidant effects. The aim of this study was to determine the effect of Moringa leaves extract and infusion on malondialdehyde (MDA) level of male obesity mice (Mus musculus) DDY strained liver induced by 2-Nitropropane. The research method was true experimental post control group design. The test subjects used were 30 male DDY strain mice aged 6-8 weeks, weighing 35-45 grams, which were divided into four groups of treatment for 20 days. Group 1 (K1): control group; Group 2 (K2): obese mice induced by 0.02mg/Kg dose of 2-Nitropropane; Group 3 (K3): obese mice given 0.2 ml/day dose of 20% Moringa leaf extract and 0.02mg/Kg dose of 2Nitropropane; Group 4 (K4): obese mice given 0.2 ml/day dose of 20% Moringa leaf infusion and 0.02mg/Kg dose of 2-Nitropropane. The antioxidant effect of Moringa leaves was measured based on the level of liver MDA using a spectrophotometer at a wavelength of 530 nm. Statistical tests were done by ANOVA and Post Hoc test with α = 0.05. Statistical analysis showed that Moringa leaf extract and infusion groups (K3 and K4) had significantly lower MDA level compared to the 2-Nitropropane (K2) group respectively (.001<0.05) and (.000<0.05). The analysis between the MDA level of extract (K3) and infusion (K4) groups of Moringa leaves did not have a significant difference (1,000> 0.05).